Cemented carbide and cutting tool

By using high-content tungsten carbide particles and bonding phases in cemented carbide and containing specific elements on its surface, the problem of shortening the life of cutting tools under difficult-to-cut materials is solved, and longer tool life and higher wear resistance are achieved.

CN119731358APending Publication Date: 2025-03-28SUMITOMO ELECTRIC INDUSTRIES LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380047054.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

During cutting processing, the difficulty of difficult-to-cut materials continues to increase, and processing conditions become more stringent, resulting in a shorter life of cutting tools.

Method used

A cemented carbide containing 80% by volume or more tungsten carbide particles and a bonding phase of 0.1% by volume or more to 20% by volume or less, and a selected first element, such as titanium, tantalum, niobium, etc., is used to ensure that the first element exists only in the surface part of the tungsten carbide particles through a specific sintering and HIP process.

Benefits of technology

The cemented carbide significantly improves the wear and defect resistance of the tool in high-speed processing of difficult-to-cut materials, thereby extending the life of the cutting tool.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731358A_ABST
    Figure CN119731358A_ABST
Patent Text Reader

Abstract

This cemented carbide is provided with a plurality of tungsten carbide particles and a binding phase, and is characterized in that the cemented carbide contains the tungsten carbide particles and the binding phase in a total amount of 80 vol% or more, and the cemented carbide contains the binding phase in an amount of 0.1-20 vol%, inclusive. The cemented carbide contains at least one first element selected from the group consisting of titanium, tantalum, niobium, zirconium, cerium, yttrium, and boron, the cemented carbide contains 0.01-20 atomic% of the first element in total, and the binder phase contains 50 mass% or more of cobalt. The result of line analysis using an energy dispersive X-ray spectroscopic device attached to a transmission electron microscope in a first direction from the bonded phases adjacent to each other toward the tungsten carbide particles is shown in the X-axis as the distance from the position at which cobalt exhibits the maximum intensity. In a first graph obtained by using a standard intensity coordinate system as an original point and a Y axis, a maximum peak M for each of the first elements exists between a peak W1 of tungsten closest to the original point and another peak W2 of tungsten closest to the peak W1, and in each of the first elements, a ratio IB / IA of an intensity IB to a maximum peak intensity IA of the maximum peak M is 0.5 or less, and a ratio IB / IA of an intensity IB to a maximum peak intensity IA of the maximum peak M is 0.5 or less. The intensity IB is an intensity of the first element at a distance P2 of 0.2 nm from a distance P1 of the maximum peak intensity IA to a side opposite to the origin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to cemented carbide and cutting tools. Background Art

[0002] Conventionally, cemented carbide having tungsten carbide (WC) particles and a binder phase containing cobalt or the like as a main component has been used as a material for cutting tools (Patent Documents 1 and 2).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2016-098393

[0006] Patent Document 2: Japanese Patent Application Publication No. 2021-110010 Summary of the invention

[0007] The cemented carbide disclosed in the present invention is a cemented carbide having a plurality of tungsten carbide particles and a bonding phase, wherein:

[0008] The cemented carbide contains 80 volume % or more of the tungsten carbide particles and the binder phase in total,

[0009] The cemented carbide contains 0.1 volume % or more and 20 volume % or less of the binder phase,

[0010] The cemented carbide comprises at least one first element selected from the group consisting of titanium, tantalum, niobium, zirconium, cerium, yttrium and boron,

[0011] The cemented carbide contains the first element in an amount of 0.01 atomic % or more and 20 atomic % or less in total,

[0012] The binding phase contains 50 mass % or more of cobalt,

[0013] The results of line analysis along a first direction from the adjacent binding phases toward the tungsten carbide particles using an energy dispersive X-ray spectrometer attached to a transmission electron microscope are shown in a first graph in which the X-axis is the distance from the position where cobalt exhibits the maximum intensity and the Y-axis is the normalized intensity.

[0014] There is a maximum peak M of each of the first elements between the peak W1 of tungsten closest to the origin and another peak W2 of tungsten closest to the peak W1.

[0015] In each of the first elements, a ratio IB / IA of the intensity IB to the maximum peak intensity IA of the maximum peak M is 0.5 or less,

[0016] The intensity IB is the intensity of the first element at a distance P2 of 0.2 nm from the distance P1 of the maximum peak intensity IA toward the opposite side of the origin. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a schematic cross-sectional view of the cemented carbide according to the first embodiment.

[0018] Figure 2 An example of a first graph showing cemented carbide according to the first embodiment.

[0019] Figure 3 This is a schematic diagram of a cutting tool according to the second embodiment. DETAILED DESCRIPTION

[0020] [Problems to be Solved by the Present Disclosure]

[0021] In recent years, in cutting, the materials being cut have become increasingly difficult to cut. Furthermore, in order to improve the processing efficiency, the cutting speed has increased, and the processing conditions have become stricter.

[0022] Therefore, an object of the present disclosure is to provide a cemented carbide that can provide a cutting tool with a long tool life when used as a tool material, especially in high-speed machining of difficult-to-cut materials, and a cutting tool with a long tool life.

[0023] [Effects of the present disclosure]

[0024] According to the present disclosure, it is possible to provide a cemented carbide that can provide a cutting tool with a long tool life when used as a material for a cutting tool, particularly in high-speed machining of difficult-to-cut materials, and a cutting tool with a long tool life.

[0025] [Description of Embodiments of the Present Disclosure]

[0026] First, embodiments of the present disclosure will be described by way of examples.

[0027] (1) The cemented carbide disclosed in the present invention is a cemented carbide having a plurality of tungsten carbide particles and a binder phase, wherein:

[0028] The cemented carbide contains 80 volume % or more of the tungsten carbide particles and the binder phase in total,

[0029] The cemented carbide contains 0.1 volume % or more and 20 volume % or less of the binder phase,

[0030] The cemented carbide comprises at least one first element selected from the group consisting of titanium, tantalum, niobium, zirconium, cerium, yttrium and boron,

[0031] The cemented carbide contains the first element in an amount of 0.01 atomic % or more and 20 atomic % or less in total,

[0032] The binding phase contains 50 mass % or more of cobalt,

[0033] The results of line analysis along a first direction from the adjacent binding phases toward the tungsten carbide particles using an energy dispersive X-ray spectrometer attached to a transmission electron microscope are shown in a first graph in which the X-axis is the distance from the position where cobalt exhibits the maximum intensity and the Y-axis is the normalized intensity.

[0034] There is a maximum peak M of each of the first elements between the peak W1 of tungsten closest to the origin and another peak W2 of tungsten closest to the peak W1.

[0035] In each of the first elements, a ratio IB / IA of the intensity IB to the maximum peak intensity IA of the maximum peak M is 0.5 or less,

[0036] The intensity IB is the intensity of the first element at a distance P2 of 0.2 nm from the distance P1 of the maximum peak intensity IA toward the opposite side of the origin.

[0037] According to the present disclosure, it is possible to provide a cemented carbide that can provide a cutting tool with a long tool life when used as a material for a cutting tool, particularly in high-speed machining of difficult-to-cut materials, and a cutting tool with a long tool life.

[0038] (2) In the above (1), the cemented carbide may contain 18 volume % or less of the binder phase. This further improves tool life.

[0039] (3) The cutting tool of the present disclosure is a cutting tool including a cutting edge made of the cemented carbide described in (1) or (2).

[0040] The cutting tools of the present disclosure can have a longer tool life.

[0041] [Details of the embodiments of the present disclosure]

[0042] Hereinafter, specific examples of the cemented carbide and cutting tool disclosed in the present invention will be described with reference to the accompanying drawings. In the accompanying drawings disclosed in the present invention, the same reference numerals represent the same parts or equivalent parts. In addition, the dimensional relationships such as length, width, thickness, depth, etc. are appropriately changed for the clarity and simplification of the accompanying drawings, and do not necessarily represent the actual dimensional relationships.

[0043] In the present disclosure, expressions in the format of “A to B” refer to the upper and lower limits of a range (i.e., greater than A and less than B). When there is no unit recorded in A and only a unit is recorded in B, the unit of A is the same as that of B.

[0044] In the present disclosure, when a compound or the like is represented by a chemical formula, unless the atomic ratio is particularly limited, all conventionally known atomic ratios are included, and the atomic ratio is not necessarily limited to the atomic ratio within the stoichiometric range.

[0045] In the present disclosure, when more than one numerical value is recorded as the lower limit and the upper limit of the numerical range, a combination of any numerical value recorded in the lower limit and any numerical value recorded in the upper limit is also disclosed. For example, when more than a1, more than b1, and more than c1 are recorded as the lower limit, and less than a2, less than b2, and less than c2 are recorded as the upper limit, more than a1 and less than a2, more than a1 and less than b2, more than a1 and less than c2, more than b1 and less than a2, more than b1 and less than b2, more than b1 and less than c2, more than c1 and less than a2, more than c1 and less than b2, more than c1 and less than c2 are disclosed.

[0046] [Embodiment 1: Cemented Carbide]

[0047] A cemented carbide according to one embodiment of the present disclosure (hereinafter also referred to as “embodiment 1”) is a cemented carbide having a plurality of tungsten carbide particles and a binder phase, wherein:

[0048] The cemented carbide contains 80 volume % or more of the tungsten carbide particles and the binder phase.

[0049] The cemented carbide contains 0.1 volume % or more and 20 volume % or less of the binder phase,

[0050] The cemented carbide comprises at least one first element selected from the group consisting of titanium, tantalum, niobium, zirconium, cerium, yttrium and boron,

[0051] The cemented carbide contains the first element in an amount of 0.01 atomic % or more and 20 atomic % or less in total,

[0052] The binder phase contains 50 mass % or more of cobalt,

[0053] The results of line analysis along a first direction from the adjacent binding phase toward the tungsten carbide particles using an energy dispersive X-ray spectrometer attached to a transmission electron microscope are shown in a first graph in which the X-axis is the distance from the position where cobalt exhibits the maximum intensity and the Y-axis is the coordinate system of the standardized intensity.

[0054] There is a maximum peak M of each of the first elements between the peak W1 of tungsten closest to the origin and the other peak W2 of tungsten closest to the peak W1.

[0055] In each of the first elements, the ratio IB / IA of the intensity IB to the maximum peak intensity IA of the maximum peak M is 0.5 or less,

[0056] The intensity IB is the intensity of the first element at a distance P2 of 0.2 nm from the distance P1 of the maximum peak intensity IA toward the opposite side of the origin.

[0057] The cemented carbide of embodiment 1 can provide the cemented carbide of the cutting tool with longer tool life when used as tool material, especially in the high-speed processing of difficult-to-cut materials, and the cutting tool with longer tool life. The reason is not clear, but it is speculated as follows.

[0058] The cemented carbide of embodiment 1 has a plurality of tungsten carbide particles (hereinafter, also referred to as "WC particles") and a binding phase, and the total content of the WC particles and the binding phase of the cemented carbide is more than 80 volume %. Thus, the cemented carbide has high hardness and high strength, and a cutting tool using the cemented carbide can have excellent wear resistance and defect resistance.

[0059] The cemented carbide of embodiment 1 contains a binder phase of 0.1 volume % or more and 20 volume % or less, and the binder phase contains 50 mass % or more of cobalt. Thus, the cemented carbide has high hardness and high strength, and a cutting tool using the cemented carbide can have excellent wear resistance and defect resistance.

[0060] The cemented carbide of embodiment 1 contains at least one first element selected from the group consisting of titanium, tantalum, niobium, zirconium, cerium, yttrium and boron in a total of 0.01 atomic % or more and 20 atomic % or less. In the first curve obtained by line analysis of the cemented carbide of embodiment 1, there is a maximum peak M of each of the first elements between the peak W1 of tungsten closest to the origin and the other peak W2 of tungsten closest to the peak W1. This indicates that the maximum concentration area of ​​the first element exists in the surface part of the tungsten carbide particles. Furthermore, the ratio IB / IA of the intensity IB to the maximum peak intensity IA is less than 0.5. This indicates that the first element exists only in the surface part of the tungsten carbide particles and does not penetrate deep into the interior of the tungsten carbide particles.

[0061] In the cemented carbide of the first embodiment, since the first element is only present in the surface layer of the tungsten carbide particles, the resistance of the cemented carbide to welding is improved. Thus, when the cemented carbide of the first embodiment is used for a cutting tool, it is possible to suppress damage such as defects caused by welding during cutting. In addition, in the cemented carbide of the first embodiment, since the first element does not penetrate deep into the interior of the tungsten carbide particles, the basic physical properties of the tungsten carbide particles, such as high hardness and high strength, are maintained without significant changes.

[0062] <Composition of cemented carbide>

[0063] like Figure 1 As shown, the cemented carbide 3 of embodiment 1 has a plurality of tungsten carbide particles 1 (hereinafter, also referred to as "WC particles") and a binding phase 2, and the total content of the WC particles and the binding phase of the cemented carbide 3 is 80 volume % or more. The lower limit of the total content of the WC particles and the binding phase of the cemented carbide can be 82 volume % or more, 84 volume % or more, 85 volume % or more, or 86 volume % or more. The upper limit of the total content of the WC particles and the binding phase of the cemented carbide can be 100 volume % or less. From the manufacturing point of view, the upper limit of the total content of the WC particles and the binding phase of the cemented carbide can be 99 volume % or less, or 98 volume % or less. The total content of the WC particles and the binding phase of the cemented carbide can be 80 volume % or more and 100 volume % or less, 82 volume % or more and 100 volume % or less, or 84 volume % or more and 100 volume % or less.

[0064] The cemented carbide of the first embodiment may be composed of a plurality of tungsten carbide particles and a binder phase. The cemented carbide of the present embodiment may further include other phases in addition to the tungsten carbide particles and the binder phase. Examples of other phases include those selected from TiCN, TiC, TiO 2 、TaC、Ta 2 O 5 、ZrC、ZrO 2 , CeC 2 、CeO 2 , YC, Y 2 O 3 , B 4 C and B 2 O 3 At least one phase in the group consisting of.

[0065] The cemented carbide of embodiment 1 can be made of tungsten carbide particles, bonding phase and other phases. The content of other phases of cemented carbide is allowed within the scope of the effect of the present disclosure. For example, the content of other phases of cemented carbide can be more than 0 volume % and less than 20 volume %, can also be more than 0 volume % and less than 18 volume %, can also be more than 0 volume % and less than 16 volume %. In this case, the total content of the WC particles of cemented carbide and bonding phase can be more than 80 volume % and less than 100 volume %, can also be more than 82 volume % and less than 100 volume %, can also be more than 84 volume % and less than 100 volume %.

[0066] The cemented carbide of embodiment 1 may contain impurities. As the impurities, for example, manganese (Mn), magnesium (Mg), calcium (Ca), and sulfur (S) can be listed. The content of impurities in the cemented carbide is allowed within the range that does not damage the effect of the present disclosure. For example, the content of impurities in the cemented carbide is preferably 0 mass % or more and less than 0.1 mass %. The content of impurities in the cemented carbide is measured by ICP emission analysis (Inductively Coupled Plasma Emission Spectroscopy (measurement device: Shimadzu Corporation "ICPS-8100" (trademark)).

[0067] The lower limit of the containing rate of the tungsten carbide particles of the cemented carbide of embodiment 1 can be more than 60 volume %, can also be more than 65 volume %, can also be more than 66 volume %, can also be more than 68 volume %.The upper limit of the containing rate of the tungsten carbide particles of this cemented carbide can be below 99.9 volume %, can also be below 99.8 volume %, can also be below 99 volume %, can also be below 98 volume %, can also be below 96 volume %, can also be below 94 volume %.The containing rate of the tungsten carbide particles of this cemented carbide can be more than 60 volume % and below 99.9 volume %, can also be more than 65 volume % and below 99.8 volume %, can also be more than 66 volume % and below 99 volume %, can also be more than 68 volume % and below 98 volume %.

[0068] The cemented carbide of embodiment 1 comprises a bonding phase of more than 0.1 volume % and less than 20 volume %. From the viewpoint of improving toughness, the lower limit of the content of the bonding phase of this cemented carbide is more than 0.1 volume %, can also be more than 1 volume %, can also be more than 2 volume %, can also be more than 3 volume %, can also be more than 5 volume %, can also be more than 8 volume %. From the viewpoint of improving hardness, the upper limit of the content of the bonding phase of this cemented carbide is less than 20 volume %, can also be less than 19 volume %, can also be less than 18 volume %, can also be less than 17 volume %, can also be less than 16 volume %, can also be less than 15 volume %. The content of the bonding phase of this cemented carbide can be more than 0.1 volume % and less than 18 volume %, can also be more than 1 volume % and less than 18 volume %, can also be more than 3 volume % and less than 17 volume %, can also be more than 5 volume % and less than 16 volume %, can also be more than 8 volume % and less than 15 volume %. When the content of the binder phase of cemented carbide is 18% by volume or less, the hardness of the cemented carbide is further improved, and the wear resistance is further improved, so that the tool life of the cutting tool using the cemented carbide as a material is further improved.

[0069] The content rate (volume %) of tungsten carbide particles in cemented carbide and the content rate (volume %) of the binder phase in cemented carbide are measured as follows.

[0070] (A1) An arbitrary position of cemented carbide is cut out to expose a cross section, and the cross section is mirror-finished using a cross-section polisher (manufactured by Nippon Denshi Co., Ltd.).

[0071] (B1) The mirror-finished surface of the cemented carbide was analyzed using a scanning electron microscope-energy dispersive X-ray spectrometry (SEM-EDX) (apparatus: Gemini 450 (trademark) manufactured by Carl Zeiss) to identify the elements contained in the cemented carbide.

[0072] (C1) The mirror-finished surface of cemented carbide was photographed using a scanning electron microscope (SEM) to obtain a reflected electron image. The photographing area of ​​the photographed image was set at the central part of the cross section of the cemented carbide, i.e., the position of the part where the properties are obviously different from the main part, such as the vicinity of the surface of the cemented carbide, which does not include the cemented carbide (the position where the photographing area is the main part of the cemented carbide). The observation magnification was 5000 times. The measurement conditions were an acceleration voltage of 3 kV, a current value of 2 nA, and a working distance (WD) of 5 mm.

[0073] (D1) The imaging region of (C1) is analyzed using an energy dispersive X-ray analyzer (SEM-EDX) attached to the SEM to determine the distribution of the elements determined in (B1) in the imaging region and obtain an element mapping image.

[0074] (E1) The reflected electron image obtained in the above (C1) is taken into a computer and binarized using image analysis software (OpenCV, SciPy). In the binarized image, the tungsten carbide particles are represented by white, and the binding phase is represented by gray to black. In addition, the threshold of binarization varies according to the contrast, so it is set for each image.

[0075] (F1) By overlapping the elemental mapping image obtained in (D1) above with the binarized image obtained in (E1) above, the existence areas of tungsten carbide particles and the binding phase are determined on the binarized image. Specifically, the area where tungsten (W) and carbon (C) exist in the elemental mapping image, which is represented by white in the binarized image, corresponds to the existence area of ​​tungsten carbide particles. The area where cobalt (Co) exists in the elemental mapping image, which is represented by gray to black in the binarized image, corresponds to the existence area of ​​the binding phase.

[0076] (G1) A rectangular measurement field of 24.9 μm×18.8 μm is set in the binarized image, and the area percentages of the tungsten carbide particles and the binder phase are measured using the image analysis software, with the area of ​​the entire measurement field as the denominator.

[0077] (H1) The measurement of (G1) is performed in five different non-overlapping measurement fields. In this specification, the average of the area percentage of tungsten carbide particles in the five measurement fields is equivalent to the content (volume %) of tungsten carbide particles in the cemented carbide, and the average of the area percentage of the binding phase in the five measurement fields is equivalent to the content (volume %) of the binding phase in the cemented carbide.

[0078] In the case where the cemented carbide contains other phases in addition to WC particles and a binding phase, the content of the other phases of the cemented carbide can be obtained by subtracting the content (volume %) of the tungsten carbide particles and the content (volume %) of the binding phase measured according to the above steps from the entire cemented carbide (100 volume %).

[0079] The following situation was confirmed: as long as it is within the scope of the applicant's measurement and as long as the measurement is performed on the same sample, even if the cut-out part of the cemented carbide section, the shooting area described in (C1) above, and the measurement field of view described in (G1) above are arbitrarily set, the content of tungsten carbide particles and the content of the binding phase in the cemented carbide are measured multiple times according to the above steps, and the deviation of the measurement results is very small. Even if the cut-out part of the cemented carbide section, the shooting area, and the measurement field of view are arbitrarily set, the results will not change arbitrarily.

[0080] <Tungsten Carbide Particles>

[0081] In Embodiment 1, the tungsten carbide particles contain tungsten carbide and a first element. In the present disclosure, the tungsten carbide particles contain the first element when, in a first curve obtained by line analysis of cemented carbide, it is confirmed that there is a maximum peak M of each of the first elements between a peak W1 of tungsten closest to the origin and another peak W2 of tungsten closest to the peak W1.

[0082] As long as the effects of the present disclosure are not impaired, the tungsten carbide particles may contain carbon, tungsten, and impurity elements other than the first element. The content of impurities in the tungsten carbide particles (when there are two or more elements constituting the impurities, the total concentration of these elements) is less than 0.1% by mass. The content of impurity elements in the tungsten carbide particles is measured by ICP emission analysis.

[0083] In Embodiment 1, the average particle size of the tungsten carbide particles is not particularly limited. The average particle size of the tungsten carbide particles can be, for example, 0.1 μm to 3.5 μm. It was confirmed that the cemented carbide of Embodiment 1 can have a long tool life regardless of the average particle size of the tungsten carbide particles.

[0084] <Combination Phase>

[0085] In embodiment 1, the bonding phase includes more than 50% by mass of cobalt. Thus, it is possible to impart excellent toughness to cemented carbide. The lower limit of the cobalt content of the bonding phase can be more than 55% by mass, can be more than 60% by mass, or can be more than 65% by mass. The upper limit of the cobalt content of the bonding phase can be less than 100% by mass, can be less than 100% by mass, can be less than 99% by mass, can be less than 98% by mass, can be less than 95% by mass, or can be less than 90% by mass. The cobalt content of the bonding phase can be more than 50% by mass and less than 100% by mass, can be more than 60% by mass and less than 99% by mass, can be more than 65% by mass and less than 98% by mass, can be more than 65% by mass and less than 95% by mass, or can be more than 65% by mass and less than 90% by mass.

[0086] The method for determining the cobalt content of the binder phase is as follows. The region where the binder phase exists is determined on the image after binarization by the same method as (A1) to (F1) of the method for determining the content of tungsten carbide particles and the content of the binder phase in the above-mentioned cemented carbide. The region where the binder phase exists is analyzed using SEM-EDX to determine the cobalt content of the binder phase.

[0087] The following situation was confirmed: as long as it is within the scope of the applicant's measurement and as long as the measurement is performed on the same sample, even if the cut-out part of the cross-section of the cemented carbide and the shooting area described in (C1) above are arbitrarily set, the cobalt content of the binding phase is measured multiple times according to the above steps, and the deviation of the measurement results is very small. Even if the cut-out part of the cross-section of the cemented carbide and the shooting area are arbitrarily set, the results will not change arbitrarily.

[0088] In the first embodiment, the binding phase may further include at least one second element selected from the group consisting of boron (B), aluminum (Al), silicon (Si), iron (Fe), nickel (Ni), germanium (Ge), ruthenium (Ru), rhenium (Re), osmium (Os), iridium (Ir), platinum (Pt), tantalum (Ta) and niobium (Nb) in addition to cobalt. The binding phase may be composed of cobalt, the second element and inevitable impurities. Examples of the inevitable impurities include manganese (Mn), magnesium (Mg), calcium (Ca), sulfur (S) and the like. The content of the inevitable impurities in the binding phase is less than 0.1% by mass. The content of the impurity elements in the binding phase is determined by ICP emission analysis.

[0089] <First Element>

[0090] The cemented carbide of embodiment 1 contains at least one first element selected from the group consisting of titanium, tantalum, niobium, zirconium, cerium, yttrium and boron. The total content of the first elements in the cemented carbide is 0.01 atomic % or more and 20 atomic % or less. Here, the total content of the first elements refers to the content of one first element when the cemented carbide contains one first element, and refers to the total content of all the first elements contained in the cemented carbide when the cemented carbide contains two or more first elements.

[0091] From the viewpoint of improving welding resistance, the lower limit of the total content of the first element of the cemented carbide is 0.01 atomic % or more, or 0.07 atomic % or more, or 0.09 atomic % or more, or 0.10 atomic % or more, or 0.50 atomic % or more, or 1.0 atomic % or more, or 3.0 atomic % or more, or 5.0 atomic % or more, or 7.0 atomic % or more. From the viewpoint of suppressing the reduction of the basic physical properties of the cemented carbide, the upper limit of the content of the first element of the cemented carbide is 20.0 atomic % or less, or 17.0 atomic % or less, or 15.0 atomic % or less, or 14.0 atomic % or less, or 10.0 atomic % or less. The total content of the first element in the cemented carbide can be greater than 0.07 atomic % and less than 17.0 atomic %, or greater than 0.09 atomic % and less than 15.0 atomic %, or greater than 0.10 atomic % and less than 15.0 atomic %, or greater than 0.50 atomic % and less than 15.0 atomic %, or greater than 1.0 atomic % and less than 14.0 atomic %, or greater than 3.0 atomic % and less than 14.0 atomic %, or greater than 5.0 atomic % and less than 10.0 atomic %, or greater than 7.0 atomic % and less than 10.0 atomic %.

[0092] The type of the first element contained in the cemented carbide and the content of the first element contained in the cemented carbide are determined by ICP emission analysis.

[0093] <Line Analysis>

[0094] use Figure 2 The results of line analysis along a first direction from mutually adjacent binder phases toward tungsten carbide particles in the cemented carbide of the first embodiment using an energy dispersive X-ray spectrometer attached to a transmission electron microscope will be described. Figure 2 is an example of a first graph, in which the elements contained in the cemented carbide, namely tungsten, cobalt and the first element (in Figure 2 The results are shown in a coordinate system where the X-axis is the distance [nm] from the position where the cobalt shows the maximum intensity and the Y-axis is the standardized intensity (standardized intensity) [au], thereby obtaining a first curve graph. Figure 2 In the cemented carbide shown in the first graph, the bonding phase is cobalt. In the first graph, the distance between the origin O and the X-axis is 0 nm, which corresponds to the position where cobalt shows the maximum intensity in the line analysis results. The standardized intensity refers to the intensity expressed relatively by taking the maximum intensity of each element in the area where the line analysis is performed as 100.

[0095] like Figure 2As shown, there is a maximum peak M of the first element between the peak W1 of tungsten closest to the origin O of the first graph and another peak W2 of tungsten closest to the peak W1. The peak W2 exists at a position farther from the origin O than the peak W1. That is, the maximum peak intensity I of the peak W1 is w1 The distance P w1 , the maximum peak intensity I of peak W2 w2 The distance P w2 , the distance P1 from the maximum peak intensity IA of the maximum peak M shows P w1 <P1<P w2 In the present disclosure, the peak intensity of the peak of each element in the first graph refers to the standardized intensity of the peak of each element.

[0096] The ratio IB / IA of the intensity IB to the maximum peak intensity IA of the maximum peak M is 0.5 or less. The intensity IB is the intensity of the first element at a position P2 with a distance of 0.2 nm from the position P1 of the maximum peak intensity to the opposite side of the origin. Figure 2 In the embodiment, the first element is one element (titanium), so there is one peak M. When the first element includes two or more elements, the maximum peak of the first element exists in the same number as the type of element, and all peaks exist between peak W1 and peak W2, and in each peak, the ratio IB / IA is less than 0.5.

[0097] The upper limit of the ratio IB / IA is 0.5 or less, 0.4 or less, 0.3 or less, 0.2 or less, or 0.1 or less. The lower limit of the ratio IB / IA may be 0 or more, 0.001 or more, 0.002 or more, 0.003 or more, 0.005 or more, 0.01 or more, 0.02 or more, or 0.05 or more. The ratio IB / IA may be 0 or more and 0.5 or less, 0.001 or more and 0.5 or less, 0.005 or more and 0.4 or less, 0.01 or more and 0.3 or less, or 0.05 or more and 0.2 or less.

[0098] In the present disclosure, the acquisition of the first curve graph based on the line analysis of cemented carbide and the analysis results is carried out according to the following steps. Using an argon ion slicer ("Low Temperature Ion Slicer IB-09060BCIS" (trademark) manufactured by JEOL Ltd.), the cemented carbide is sliced ​​into a thickness of 30 to 100 nm under the conditions of an acceleration voltage of 6 kV and a finishing of 2 kV to prepare a sample for measurement. Next, using a TEM (Transmission Electron Microscopy) ("JEM-ARM300F2" (trademark) manufactured by JEOL Ltd.), the sample for measurement is observed at 200,000 times under the conditions of an acceleration voltage of 200 V, thereby obtaining a first image (not shown).

[0099] In the first image, the tungsten carbide particles are observed as white areas, and the binder phase is observed as black areas. In the first image, the interface between the tungsten carbide particles and the binder phase is arbitrarily selected.

[0100] Next, the selected interface is positioned in a manner near the center of the image, and the observation magnification is adjusted to observe in a manner of a field of view size of 10nm×10nm, thereby obtaining a second image (not shown). In the second image, the elongation direction of the interface elongation is confirmed. Along a direction perpendicular to the elongation direction, and from a position X1 disposed in the binding phase toward a first direction of a position X2 disposed in a tungsten carbide particle adjacent to the binding phase, a line analysis is performed using an energy dispersive X-ray spectrometer (TEM-EDX) attached to a transmission electron microscope, and the distribution of tungsten, cobalt, and the first element is measured. Here, the direction perpendicular to the elongation direction of the interface refers to the direction of a straight line intersecting at an angle of 90°±5° along a tangent to the elongation direction. The position X1 in the binding phase is set in the first curve diagram at a position where the peak of cobalt can be confirmed at a distance of 0.5nm or more and 5nm or less from the distance P1 of the peak M to the origin side. The position X2 in the tungsten carbide particle is set to a position where the distance from the peak M to the opposite side of the origin is 2 nm or more and 5 nm or less in the first graph. The conditions for EDX implementation are an acceleration voltage of 200 kV, a camera length of 10 cm, a pixel count of 128×128 pixels, and a dwell time of 0.02 to 3 s / pixel.

[0101] The measurement results of each of tungsten, cobalt, and the first element are plotted in a coordinate system where the X-axis represents the distance from the position where cobalt exhibits the maximum intensity and the Y-axis represents the normalized intensity, thereby obtaining a first graph.

[0102] In cemented carbide, five non-overlapping first images of the visual field are randomly obtained, and the above analysis is performed based on each first image to obtain five first curves. In more than four first curves, when "there is a maximum peak M of each of the first elements between peak W1 and peak W2, and the ratio IB / IA is less than 0.5", in the first curve of the cemented carbide, it is judged that "there is a maximum peak M of each of the first elements between peak W1 and peak W2, and the ratio IB / IA is less than 0.5". In order to obtain this judgment criterion, the inventor of the present invention conducted multiple line analyses on multiple cemented carbides respectively. As a result, it was confirmed that in more than 80% of the first curves in the cemented carbide, when "there is a maximum peak M of each of the first elements between peak W1 and peak W2, and the ratio IB / IA is less than 0.5", the cemented carbide showed the effect of the present disclosure. If the manufacturing method of cemented carbide is taken into consideration, it is inferred that the existence form of tungsten and the first element in the interface region between WC particles and the binding phase is roughly the same in the same cemented carbide.

[0103] <Method for manufacturing cemented carbide>

[0104] The cemented carbide of the present embodiment can be produced by sequentially performing a raw material powder preparation step, a mixing step, a molding step, a sintering step, a cooling step, and a HIP step.

[0105] <Preparation process>

[0106] The preparation step is a step of preparing raw material powder of the material constituting the cemented carbide raw material. Examples of the raw material powder include tungsten carbide powder (hereinafter, also referred to as "WC powder"), cobalt (Co) powder, and powder containing the first element. Examples of the powder containing the first element include TiCN powder, TaC powder, NbC powder, ZrC powder, CeC powder, etc. 2 Powder, Y 2 O 3 Powder, B 4 C powder. In addition to these raw material powders, nickel (Ni) powder and the like can also be prepared. These raw material powders can use commercially available products. The average particle size of these raw material powders is not particularly limited, and can be set to 0.1 to 3.0 μm, for example. The average particle size of the raw material powder refers to the average particle size measured by the FSSS method (Fisher Sub-Sieve Sizer: Fisher particle size measurement method). The average particle size is measured using the "Sub-Sieve Sizer Model 95" (trademark) manufactured by Fisher Scientific.

[0107] <Mixing process>

[0108] The mixing process is a process of mixing the respective raw material powders prepared in the preparation process in a predetermined ratio. Through the mixing process, a mixed powder formed by mixing the respective raw material powders is obtained. The mixing ratio of the respective raw material powders is appropriately adjusted according to the composition of the target cemented carbide.

[0109] The mixing of the respective raw material powders can be performed using a ball mill. The mixing conditions can be set, for example, as a medium diameter of 6 mm, a rotation speed of 100 rpm, and a mixing time of 20 hours.

[0110] After the mixing process, granulation of the mixed powder can be performed as needed. By granulating the mixed powder, it becomes easy to fill the mixed powder into a die head or a mold in the subsequent forming process. Granulation can employ a known granulation method, and for example, a commercially available granulator such as a spray dryer can be used.

[0111] <Forming Process>

[0112] The forming process is a process of forming the mixed powder obtained in the mixing process into a shape for a cutting tool to obtain a formed body. The forming method and forming conditions in the forming process may be general methods and conditions and are not particularly limited.

[0113] <Sintering Process>

[0114] In the sintering process, the formed body obtained in the forming process is sintered to obtain a cemented carbide. In the method for manufacturing a cemented carbide of the present disclosure, first, it is held in Ar gas at a pressure of 0.1 MPa and a temperature of 1400 °C for 400 minutes (hereinafter, also referred to as "the first sintering process"), and then, it is held in Ar gas at a pressure of 5 MPa and a temperature of 1350 °C for 300 minutes (hereinafter, also referred to as "the second sintering process") to sinter the formed body and obtain a cemented carbide intermediate.

[0115] <Cooling Process>

[0116] The cooling process is a process of cooling the cemented carbide intermediate after the sintering process. For example, the above-mentioned cemented carbide intermediate can be quenched in Ar gas under the condition of a pressure of 100 to 400 MPaG.

[0117] <HIP Process>

[0118] A pressure of 10 MPa is applied to the cooled cemented carbide intermediate for 60 minutes using a hot isostatic pressing (HIP) device. Thereby, a cemented carbide can be obtained.

[0119] <Features of the Method for Manufacturing a Cemented Carbide of the Present Embodiment>

[0120] In the present embodiment, the mixing process is carried out for 20 hours using a ball mill, and the sintering process is carried out in two stages: first, the mixture is kept at a pressure of 0.1 MPa and a temperature of 1400°C for 400 minutes (the first sintering process), and then, the mixture is kept at a pressure of 5 MPa and a temperature of 1350°C for 300 minutes (the second sintering process). From this, it can be inferred that the first curve diagram of the obtained cemented carbide shows that "there is a maximum peak M of each of the first element between peak W1 and peak W2, and the ratio IB / IA is less than 0.5". The inventors of the present invention have conducted in-depth research and have newly discovered that the cemented carbide disclosed in the present invention can be achieved by such mixing conditions and sintering conditions. In addition, the mixing conditions and sintering conditions used in the present embodiment are not adopted by those skilled in the art because of the reduced production efficiency.

[0121] In the conventional manufacturing method of cemented carbide, the mixing time is about 10 hours, and the sintering process is carried out in a stage of maintaining the predetermined time after heating to a predetermined temperature. In the cemented carbide obtained by the conventional manufacturing method of cemented carbide, the first element is randomly arranged in the interface region between the WC particles and the binding phase, and in the first curve, there is no maximum peak M of each of the first element between the peak W1 and the peak W2.

[0122] [Embodiment 2: Cutting tool]

[0123] The cutting tool of this embodiment includes a blade tip made of cemented carbide of Embodiment 1. In this disclosure, the blade tip refers to a portion involved in cutting. More specifically, the blade tip refers to a region surrounded by a blade tip ridgeline and an imaginary surface with a distance of 0.5 mm or 2 mm from the blade tip ridgeline toward the cemented carbide side.

[0124] Examples of cutting tools include cutting tools, drills, end mills, indexable cutting inserts for milling, indexable cutting inserts for turning, metalworking saws, gear cutting tools, reamers, taps, and the like. In particular, Figure 3 As shown, the cutting tool 10 of the present embodiment can exert excellent effects when it is a small-diameter drill for processing a printed circuit board. Figure 3 The cutting edge 11 of the cutting tool 10 shown is made of the cemented carbide of the first embodiment.

[0125] The cemented carbide of this embodiment may constitute the whole of these tools or a part thereof. Here, "constituting a part" means a method of forming a cutting edge portion by brazing the cemented carbide of this embodiment to a predetermined position of any base material.

[0126] The cutting tool of the present embodiment may further include a hard film covering at least a portion of the surface of the substrate made of cemented carbide. As the hard film, for example, diamond-like carbon or diamond may be used.

[0127] The cemented carbide of the first embodiment can be formed into a desired shape to obtain the cutting tool of the present embodiment.

[0128] Example

[0129] The present embodiment will be described in more detail by way of examples, but the present embodiment is not limited to these examples.

[0130] [Production of cemented carbide]

[0131] The cemented carbide of each sample was produced according to the following procedure.

[0132] WC powder (average particle size 0.5 μm), Co powder (average particle size 1.0 μm), TiCN powder (average particle size 0.1 μm), TaC powder (average particle size 0.3 μm), NbC powder (average particle size 0.3 μm), ZrC powder (average particle size 0.5 μm), CeC powder (average particle size 0.5 μm) were prepared in the proportions described in the "Raw material powder" column of Tables 1 to 3. 2 Powder (average particle size 0.5 μm), Y 2 O 3 Powder (average particle size 0.5 μm), B 4 C powder (average particle size 0.5 μm).

[0133] Table 1

[0134]

[0135] Table 2

[0136]

[0137] Table 3

[0138]

[0139] The raw material powders were mixed in a bead mill to obtain a mixed powder. The mixing conditions (media diameter, rotation speed, filling rate, time) were as follows. "Filling rate" refers to the bead filling rate.

[0140] 《Sample 1 to Sample 48》

[0141] The medium diameter was 6 mm, the rotation speed was 100 rpm, the filling rate was 40%, and the mixing time was 20 hours.

[0142] 《Specimens 49 to 76》

[0143] The medium diameter was 6 mm, the rotation speed was 100 rpm, the filling rate was 40%, and the mixing time was 10 hours.

[0144] Next, the mixed powder was press-formed to produce a molded body in the shape of a cutting blade. Next, the molded body was sintered to obtain a cemented carbide intermediate. The sintering conditions for each sample were as follows.

[0145] 《Sample 1 to Sample 48》

[0146] First sintering step: maintaining the temperature at 1400° C. in Ar gas at a pressure of 0.1 MPa for 400 minutes.

[0147] Second sintering step: maintaining the temperature at 1350° C. in Ar gas at a pressure of 5 MPa for 300 minutes.

[0148] 《Specimens 49 to 76》

[0149] First sintering step: maintaining the temperature at 1400° C. in Ar gas at a pressure of 0.1 MPa for 60 minutes.

[0150] Second sintering process: None.

[0151] "The first sintering process" refers to the sintering process performed after the sintering starts. "The second sintering process" refers to the second stage sintering process performed after the first sintering process. The record of "none" for the second sintering process indicates that the second sintering process is not performed. Next, the cemented carbide intermediate is rapidly cooled under a pressure of 200 MPaG in Ar gas. A hot isostatic pressing (HIP) device is used to apply a pressure of 10 MPa for 60 minutes to the cooled cemented carbide intermediate. Thus, the cemented carbide of each sample is obtained.

[0152] [Manufacturing of cutting tools]

[0153] The obtained cemented carbide was processed to produce an indexable cutting tool (shape: end mill).

[0154] [Evaluation of cemented carbide]

[0155] <Content Rate (Volume %) of Tungsten Carbide Particles and Content Rate (Volume %) of Binder Phase in Cemented Carbide>

[0156] The content rate (volume %) of tungsten carbide particles and the content rate (volume %) of the binding phase of the cemented carbide of each sample are measured. The specific measurement method is as described in Implementation Example 1. The results are shown in the "WC particle content rate" and "binding phase content rate" columns of "cemented carbide" in Tables 4 to 6. Furthermore, the total content rate of tungsten carbide particles and the content rate of the binding phase of the cemented carbide is shown in the "WC particle + binding phase content rate" column of "cemented carbide" in Tables 4 to 6. In Tables 4 to 6, it is confirmed that the cemented carbide with a volume % lower than 100% in the "WC particle + binding phase content rate" column contains precipitates, solid solutions (such as TiCN, TaC), etc. of compounds containing the first element.

[0157] <Cobalt Content in Binder Phase>

[0158] The cobalt content in the binder phase was measured in the cemented carbide of each sample. The specific measurement method is as described in Embodiment 1. The results are shown in the "Co content in binder phase" column of "cemented carbide" in Tables 4 to 6.

[0159] <Total content of first element in cemented carbide>

[0160] The type and total content of the first element in the cemented carbide of each sample were measured. The specific measurement method is as described in Embodiment 1. The results are shown in the "Type of First Element" and "Total Content of First Element" columns of "Cemented Carbide" in Tables 7 to 9.

[0161] <Line Analysis>

[0162] In the cemented carbide of each sample, the line analysis shown in embodiment 1 is performed to obtain a first curve graph. In the first curve graph of each sample, it is confirmed whether there is a maximum peak M of each of the first elements between the peak W1 of tungsten closest to the origin and the other peak W2 of tungsten closest to peak W1. The results are shown in the "Maximum Peak M" column of "Cemented Carbide" in Tables 7 to 9. "Yes" indicates the presence of the maximum peak M, and "No" indicates the absence of the maximum peak M. In the case where there are multiple maximum peaks M, "Yes" is indicated when all the maximum peaks are between W1 and W2.

[0163] In the sample with the "maximum peak M", the ratio IB / IA of the intensity IB to the maximum peak intensity IA of the maximum peak M was measured. Here, the intensity IB is the normalized intensity of the first element at the position P2 which is 0.2 nm away from the position P1 of the maximum peak intensity to the side opposite to the origin of the first curve. The results are shown in the "IB / IA" column of "hard alloy" in Tables 7 to 9.

[0164] Table 4

[0165]

[0166] Table 5

[0167]

[0168] Table 6

[0169]

[0170] Table 7

[0171]

[0172] Table 8

[0173]

[0174] Table 9

[0175]

[0176] <Cutting test>

[0177] The cutting tool of each sample was used for end milling under the following conditions, and the damage width of the back face was measured every 0.01m of cutting distance. The damage width refers to the maximum length of the damage on the back face caused by wear and cracking. The maximum length is equivalent to the maximum wear amount in the case of wear, and the maximum defect length in the case of cracking. The cutting distance at the time point when the damage width reaches 0.1mm is taken as the tool life. The results are shown in the "Cutting Test" column of Tables 7 to 9. The longer the cutting distance, the longer the tool life.

[0178] 《Cutting conditions》

[0179] Workpiece: Inconel

[0180] Processing: Side processing

[0181] Cutting speed: 120m / min

[0182] Feed rate per blade fz: 0.1mm / t

[0183] Axial penetration depth ap: 0.2mm

[0184] Radial cutting depth ae: 0.2mm

[0185] Cutting fluid: water-soluble cutting oil

[0186] The above cutting conditions are equivalent to high-speed machining of difficult-to-cut materials.

[0187] <Inspection>

[0188] The cemented carbides and cutting tools of samples 1 to 48 correspond to the embodiments. The cemented carbides and cutting tools of samples 49 to 76 correspond to the comparative examples. The cutting tools of samples 1 to 48 (embodiments) were confirmed to have a longer tool life in high-speed machining of difficult-to-cut materials compared to the cutting tools of samples 49 to 76 (comparative examples). It is presumed that this is because the cemented carbides of samples 1 to 48 (embodiments) have a peak M and a ratio IB / IA of 0.5 or less, so the resistance to welding is improved, and the occurrence of wear and defects associated with welding is suppressed.

[0189] As mentioned above, although the embodiment and the example of this disclosure were described, it is also planned from the beginning that the configurations of each embodiment and the example described above are appropriately combined or variously modified.

[0190] The embodiments and examples disclosed herein are illustrative in all aspects and are not restrictive. The scope of the present invention is indicated by the claims rather than the embodiments and is intended to include all modifications within the scope and meaning equivalent to the claims.

[0191] Description of Reference Numerals

[0192] 1: tungsten carbide particles; 2: bonding phase; 3: cemented carbide; 10: cutting tool; 11: tool tip.

Claims

1. A cemented carbide comprising a plurality of tungsten carbide particles and a binding phase, wherein: The cemented carbide contains 80 volume % or more of the tungsten carbide particles and the binder phase in total, The cemented carbide contains 0.1 volume % or more and 20 volume % or less of the binder phase, The cemented carbide comprises at least one first element selected from the group consisting of titanium, tantalum, niobium, zirconium, cerium, yttrium and boron, The cemented carbide contains the first element in an amount of 0.01 atomic % or more and 20 atomic % or less in total, The binding phase contains 50 mass % or more of cobalt, The results of line analysis along a first direction from the adjacent binding phases toward the tungsten carbide particles using an energy dispersive X-ray spectrometer attached to a transmission electron microscope are shown in a first graph in which the X-axis is the distance from the position where cobalt exhibits the maximum intensity and the Y-axis is the normalized intensity. There is a maximum peak M of each of the first elements between the peak W1 of tungsten closest to the origin and another peak W2 of tungsten closest to the peak W1. In each of the first elements, a ratio IB / IA of the intensity IB to the maximum peak intensity IA of the maximum peak M is 0.5 or less, The intensity IB is the intensity of the first element at a distance P2 of 0.2 nm from the distance P1 of the maximum peak intensity IA toward the opposite side of the origin.

2. The cemented carbide according to claim 1, wherein: The cemented carbide contains 18 volume % or less of the binder phase.

3. A cutting tool comprising a cutting edge made of the cemented carbide according to claim 1 or 2.

Citation Information

Patent Citations

  • Hard metal alloy

    JP2016098393A

  • Ultrafine particle cemented carbide, and tool for cutting or cutting grinding or tool for wear resistance using the same

    JP2021110010A